Matematyka, matematyka finansowa i inżynieria finansowa realizowane na kierunkach ekonomicznych w świetle obowiązujących standardów nauczania - Górska, Anna; Kozioł-Kaczorek, Dorota (Mathematics, financial mathematics and financial engineering carried out on the field of economics in light of the existing standards teaching, 2011)
Problems associated with the implementation of mathematical subjects on the Faculty of Economic Sciences (Warsaw University of Life Sciences) are presented in this paper. These subjects are mathematics, financial mathematics and financial engineering. The presented considerations are based on the experience gained during lectures and exercises listed direction of study: Economics, Management, Logistics, Finance and Accounting
Didactics of Mathematics, 2011, Nr 8 (12), s. 31-37
Keywords: financial mathematics; financial engineering; teaching standards; core curriculum; economic studies